COMPARISON OF HEMODYNAMIC EFFECTS OF INHALATORY ILOPROST AND NITRIC OXIDE IN PATIENTS WITH SEVERE LEFT VENTRICLE DYSFUNCTION - A. E. Bautin; A. S. Yakovlev; S. V. Zayashnikov; D. M. Tashkhanov; A. O. Marichev; P. A. Fedotov; M. А. Bortsova; Yu. V. Sazonova; I. V. Sukhova; I. E. Titova; M. A. Simonenko; M. Yu. Sitnikova; et al. (Российский кардиологический журнал)
Aim. To compare the effect of nitric oxide (NO) and inhalatory iloprost (IIP) on the hemodynamics of pulmonary hypertension patients, associated with severe systolic dysfunction of the left ventricle (LV).Material and methods. A retrospective description research performed, of the results of 158 consequently done tests for reversibility of pulmonary hypertension with NO and IIP in 124 candidates for cardiac transplantation, with pulmonary vascular resistance (PVR) more than 2,5 units of Wood. Totally, 32 females and 92 males investigated (mean age 48,9±11,2 y. o.) with heart failure (HF) of ischemic (n=59) and non-coronary (n=65) origin, with the LF ejection fraction 22,5±5,2%. Inhalation of NO in 80 ppm concentration was applied in 47 cases (39 patients), IIP with dosage 20 mcg — in 111 cases (93 patients). Pressure measurement in pulmonary artery (PA) and hemodynamics parameters was done with Swan-Ganz catheter. The data presented as the mean ± standard deviation.Results. Decrease of the mean pressure in PA was noted: at NO from 34,7±8,4 to 32,7±9,7 mmHg (p=0,015), IIP from 36,7±10 to 31,1±9,2 mmHg (p<0,001). Pulmonary resistance decreased at NO from 4,8±1,7 to 3,6±1,6 Wood units (p<0,001) and IIP — from 4,9±2 to 3,1±1,4 Wood units (p<0,001). With NO, total peripheral vascular resistance (TPVR) and blood pressure (BP) did not change, but IIP decreased TPVR from 1772±495 to 1445±444 dyn·sec·cm-5 (p<0,001) and BPav from 79,7±10 to 74,8±11,5 mmHg (p<0,001). NO caused mild overload on the LV: PA wedge pressure increased from 19,6±6,5 to 21,2±7,9 mmHg (p=0,038), contrary, IIP decreased wedge pressure from 20,2±6,5 to 18,7±6,6 mmHg (p<0,001). Increase of preand postload at NO inhalation led to decrease of the stroke volume index (SVI) from 23,8±7,9 to 22,4±6,3 mL/m2 (p=0,023). And IIP increased SVI from 26,2±7,2 to 30,7±8,7 mL/m2 (p<0,001).Conclusion. In patients with severe systolic dysfunction of the LV, IIP (contrary to NO) positively influenced the injured LV.